Emotional awareness, mood and individual and social adjustment outcomes in children aged 8-12 years old - Villanueva, Lidón; Prado-Gascó, Vicente; González-Barrón, Remedios; Montoya, Inmaculada (Anales de Psicología / Annals of Psychology, 2014)
Emotional awareness or conscious experience of emotion is a key concept related to different individual adjustment child outcomes, such as somatic complaints. This relationship, moderated by mood, has been found in preadolescent and adolescent population. However, little is known in younger children and including other adjustment outcomes, such as adaptation. Therefore, the objective of this work is to analyze the contribution of emotional awareness and mood upon different adjustment outcomes: somatic complaints and inadaptation (assessed by the test TAMAI), in children aged 8-12 years old. Different self-reported questionnaires were administered to 1423 children, with a mean age of 9.8 years old. Results support the influence of emotional awareness (mainly the ability to differentiate emotions and analyze the own emotions), strengthened by mood, not only upon somatic complaints, but also upon personal and social inadaptation. These results come to outline the importance of emotional abilities and the corresponding affective moods, in children daily life.